REAKSI PASAR MODAL INDONESIA TERHADAP PELUNCURAN BURSA KARBON INDONESIA PADA 26 SEPTEMBER 2023: Indonesia - Gunawan, Aldira Zulfa; Sembiring, Ferikawita M (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research is an event study which aims to analyze the conditions and differences in abnormal returns, market capitalization, security return variability and stock volatility before and after the launch of the Indonesian Carbon Exchange on 26 September 2023 in the energy sector listed on the Indonesian Stock Exchange (BEI). The research method used is quatitative method. The sampling method is purposive sampling where there were 39 energy companies that were the research sample with the observation period used being 11 stock exchange days, which were processed using Microsoft Excel and SPSS 26. In this research, descriptive statistical test techniques were used, the normality test (Kolmogrov Smirnov test), reaction test (one sample Kolmogrov Smirnov), different test (Wilcoxon and paired sample t test). The results of this research show that there are abnormal returns around the launch of the Indonesian Carbon Exchange, there are significant differences in abnormal returns and market capitalization around the launch of the carbon exchange, but there is no difference in security return variability, stock volatility around the launch of the Indonesian Carbon Exchange.